A Hybrid Method for the Solution of Some Multi-Commodity Spatial Equilibrium Problems - Pang, Jong-Shi (Management Science, 1981)
This paper describes a hybrid method for solving the multi-commodity transportation and transshipment spatial equilibrium models. The method is basically a specialization of the block successive overrelaxation method for solving a linear complementarity problem with certain block structure and consists of solving a sequence of subproblems of the single-commodity type. These subproblems are solved by a special-purpose principal pivoting algorithm developed in an earlier paper. Under some mild conditions, convergence of the proposed method is established. Finally, computational experience of solving some fairly large randomly generated problems by the proposed hybrid method is presented.